Spoiled Rotten? LMXSC Motivates Greater Supervisor-Directed Deviance in Individuals Who Were Overindulged as Children - Benjamin A. Korman (Journal of Business and Psychology, 2024)
Recent work has demonstrated that perceiving oneself as being treated better by one's leader compared to one's coworkers' treatment by the same leader (i.e., leader-member exchange social comparison; LMXSC) can motivate aggressive behavior towards one's colleagues. Extending these findings, the current paper argues that high LMXSC employees can also be motivated to show aggressive behavior towards their leader, depending on their early experiences with authority figures (i.e., parents/guardians). Using both experimental and time-lagged field study designs, this study demonstrates that LMXSC elicits hubristic pride which, in turn, motivates supervisor-directed deviance in subordinates who were overindulged by their parents/guardians as children. These findings challenge the assumption that high LMXSC employees reciprocate their leaders' positive treatment by revealing when and why they can be motivated to demonstrate aggressive and deviant leader-directed behavior.
Keywords: 650; Leader-member exchange social comparison (LMXSC); Hubristic pride; Parental overindulgence; Supervisor-directed deviance